Genetic structure, mating system and domestication of annatto (Bixa orellana L.) using molecular markers - Dequigiovanni, Gabriel (2017)
Plant domestication is an evolutionary process that leads to several modifications in plants to increase adaptation to cultivation and utilization by humans. These modifications may decrease the fitness of plants in the wild habitat but increase it for human exploitation. Annatto (Bixa orellana L.) is a shrubby plant domesticated in Amazonia from wild annatto (Bixa orellana var. urucurana) populations. This thesis presents a more in-depth understanding of the domestication, mating system and genetic diversity and structure of annatto and its wild ancestor in Brazil. In the first study, a new set of 32 microsatellite loci isolated from a microsatellite-enriched genomic library was developed, of which 12 were polymorphic in populations of both cultivated and wild annatto. In the second study, the genetic diversity and structure of wild annatto populations in Brazilian Amazonia were characterized with 16 microsatellite markers. High population structure and positive correlation between genetic and geographic distances were found, suggesting that genetic differentiation might be caused by geographic isolation. Additionally, Ecological Niche Modeling was used to characterize the potential geographical range of this variety in northern South America and detected that South Rondônia, Madre di Dios River basin, Llanos de Mojos, Llanos de Orinoco and eastern Ecuador are highly suitable areas for wild annatto to occur, providing additional targets for future exploration and conservation. In the third study, 16 microsatellite loci and four phytochemical compounds were used to evaluate the genetic diversity of 63 accessions from the annatto germplasm bank at the Agronomic Institute (IAC). In both molecular and phytochemical analysis the results tended to separate the accessions from Rondônia, northern Brazil, from the Southwestern accessions. Rondônia accessions showed higher values for all the phytochemical compounds and higher levels of genetic diversity. Some accessions presented bixin levels well above the average and are promising materials to be used in genetic improvement programs. In the fourth study, 12 microsatellite loci were used to determine the mating system of a cultivated population of annatto from Rondon do Pará, PA. Multilocus outcrossing rate indicated a mixed mating system for this population. Biparental inbreeding also contributed to the selfing rate in this population. Crossings among related individuals were also observed. Due to this mixed breeding system, the collection of open-pollinated seeds for plant breeding or conservation purposes should include at least 60 plants to ensure a representative sample. In the fifth study, the amount and distribution of genetic diversity among samples of cultivated annatto from homegardens of riverside communities along the major rivers in Brazilian Amazonia, and from farmer´s fields along highways, in the States of Rondônia and Pará, and Southeastern Brazil was characterized. The samples collected presented moderate levels of genetic diversity, and moderate to high levels of admixture between geographic groups, occurring mainly due to exchange of seeds among farmers. However, cluster and Bayesian analyses showed a tendency to group samples based on their geographic origin. Isolation by distance was observed, according to Mantel\'s test. In the last study, wild and cultivated annatto samples from Brazilian Amazonia were compared using 16 microsatellite loci and two cpDNA regions. A clear separation between wild and cultivated annatto, supported by high values of FST in both analyses was observed. Wild samples presented higher rates of diversity in relation to cultivated, partly because these populations did not suffer anthropic selection, as in the cultivated varieties. The data suggest the existence of genetic relationship between wild and cultivated annatto, indicated by moderate levels of gene flow. The results also showed the proximity between groups of cultivated and wild accessions from Rondônia and the Madeira River basin. This proximity provides indications that annatto started its domestication in this area from B. orellana var. urucurana.